2012
DOI: 10.1111/j.1556-4029.2012.02234.x
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Behavior in Opioid‐Dependent Patients Before and During Maintenance Therapy: 6‐year Follow‐Up of a Nationally Representative Cohort Sample

Abstract: Lifetime prevalence of opioid dependence is about 0.4% in western countries. Opioid-dependent patients have high morbidity and mortality and a high risk of criminal behavior. Few studies have addressed the long-term impact of opioid maintenance therapy on convictions and criminal behavior. The PREMOS study is a prospective, longitudinal, naturalistic clinical study of a nationally representative sample of 2694 opioid-dependent patients to investigate convictions and criminal behavior at baseline and after 6 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 66 publications
(91 reference statements)
1
10
1
1
Order By: Relevance
“…These results reinforce findings from other national and international studies (Oliveira and Souza 2013;Paim Kessler et al 2012;Silva et al 2012;Zweig, Yahner, and Rossman 2012). In these studies, the crime rate varied from 23% to 97% according to the profile of the population with substance dependence (for example, different DOCs, different age ranges), the data collection setting, and the types of crime investigated (Carvalho and Seibel 2009;Fernández-Montalvo et al 2013;Johnson et al 2013;Soyka et al 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results reinforce findings from other national and international studies (Oliveira and Souza 2013;Paim Kessler et al 2012;Silva et al 2012;Zweig, Yahner, and Rossman 2012). In these studies, the crime rate varied from 23% to 97% according to the profile of the population with substance dependence (for example, different DOCs, different age ranges), the data collection setting, and the types of crime investigated (Carvalho and Seibel 2009;Fernández-Montalvo et al 2013;Johnson et al 2013;Soyka et al 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Crack use is generally concentrated among disenfranchised young people with crime involvement (Johnson et al 2013;Paim Kessler et al 2012;Rodrigues et al 2012;Soyka et al 2012). However, in the present study, the presence of a severe drug problem increased the likelihood of that person having committed a crime (Volkmann et al 2013) against persons or property.…”
Section: Discussioncontrasting
confidence: 56%
“…This includes the need for the development, implementation, and evaluation of effective psycho-social and pharmacological therapies, which have not emerged thus far (32). Improving addiction treatment access and options for youth who use stimulants can be expected to reduce engagement in drug dealing along with other risky income generating activities (33,34). …”
Section: Discussionmentioning
confidence: 99%
“…[4,14] Findings from a recent study by Sokya et al [15] show a significant rate of criminal activity and convictions in patients entering opioid-substitution treatment and a decrease in criminal activities over time. Gossop et al [5] also showed that longer periods of stay in methadone treatment were linked to greater reductions in both heroin use and criminal activity.…”
Section: Articlementioning
confidence: 98%